Suitability of Natura 2000 sites for threatened freshwater species under projected climate change. Issue 12 (24th November 2022) - Basen, Timo; Chucholl, Christoph; Oexle, Sarah; Ros, Albert; Brinker, Alexander
Abstract: As part of the world's largest coordinated network of protected areas, Natura 2000, European Union member states designate special areas of conservation (SACs) to maintain or achieve favourable conservation status for imperilled aquatic species listed under Annex II of the Habitats Directive. Long‐term suitability of SAC habitats is potentially challenged by continuing climate change. To examine this emerging threat to aquatic species conservation, the habitat suitability of designated SACs (n = 8, 221) for 24 Central European freshwater species (18 teleosts, two lampreys, two crayfish and two bivalves) was assessed under current and projected end‐of‐century climate using environmental niche models calibrated on species occurrences reported under the Habitats Directive (n = 33, 995). Potential future conditions included three climate‐change scenarios representing a gradient from effective climate protection measures to a worst‐case warming scenario. Habitat suitability of SACs was consistently calculated as high under present climate but projected to decline severely for two‐thirds of the species under future climate conditions, with the magnitude of decline generally paralleling that of projected climate change. Under high emission scenarios, one third to more than half of the species were predicted to face unsuitable conditions in ≥75% of SACs. Predicted change in habitat suitability varied across biogeographical regions, with Alpine SACs often undergoing lower or no decline in predicted suitability. Given the discrepancy between the location of currently designated SACs and predicted areas of suitable habitat under projected end‐of‐century climate, climate change can be expected to undermine the long‐term effectiveness of currently protected areas. Fostering climate resilience of freshwater habitats within SACs, restoring stream connectivity among SACs, assisted migration to newly suitable SACs where natural dispersal is not possible, as well as designation of new protected areas within climate refugia represent key actions to overcome this potential future conservation gap.